E-Learning Implementation as a Support Teaching Learning Processes for Lecturers and Students in Universitas Pembangunan Nasional “ Veteran” Jawa Timur - Nuruni I. K.W; Sishadiyati; Zumrotul F. (Future Science)
Current technological developments are increasingly advanced and sophisticated both in education and business. With the development of these technologies, it is expected that in the University of East Java's National Development in the teaching and learning process can also implement by following the development of these technologies. In the environment of UPN